Effectiveness of exercise intervention on children and adolescents with depression: a systematic review and meta-analysis of randomized controlled trial - Yan, Haoming; Chen, Rui; Chen, Daiwei; Li, Changdong (Frontiers in Psychiatry, 2025)
ObjectiveThe increasing occurrence of depression in children and teenagers has garnered significant social attention. Although many studies have explored the effect of exercise on alleviating depressive symptoms, substantial evidence regarding its efficacy in children and adolescents with clinical diagnoses of depression remains insufficient. This research performs a systematic review and meta-analysis aimed at assessing the true effectiveness of exercise interventions for this demographic.MethodsWe searched five databases (PubMed, Embase, Cochrane, EBSCO, and Web of Science) for studies available up to August 18, 2025. All data analyses were conducted using Review Manager software. Four subgroup analyses were carried out according to exercise frequency, session length, duration of the intervention, and control group type in order to identify the sources of variability.ResultsFollowing a thorough review of the 2,475 articles that were initially identified, a total of 15 studies were finally incorporated into the meta-analysis. These studies included 428 participants in the groups receiving exercise interventions and 403 participants in the control groups. The findings indicated that exercise produced a notable beneficial impact on children and adolescents suffering from depression (SMD = -1.14, 95% CI: -1.57 to -0.72, p < 0.001). Subgroup analyses further revealed that different weekly exercise frequencies, session durations, and intervention periods all demonstrated statistically significant beneficial effects on depressive symptoms. Moreover, exercise interventions achieved therapeutic effects comparable to those of conventional treatments.ConclusionExercise interventions were found to offer substantial therapeutic benefits for depressed children and adolescents in this study. Interventions performed more than three times per week, lasting less than 60 minutes per session, and sustained over eight weeks were found to be the most effective. Compared with traditional treatment approaches, exercise interventions achieved similarly positive outcomes. These findings provide strong evidence for optimizing exercise prescriptions and health management strategies for adolescent mental health. Educators, parents, and school administrators should incorporate age-appropriate physical activities into daily life and design exercise programs with suitable frequency, duration, and intensity.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251121698.